Emerging Trends in Visual Secret Sharing - Yadav, Mainejar; ., Ranvijay (International Journal of Engineering and Technology, 2018)
Visual Secret Sharing (VSS) is an increased applicability of traditional secret sharing. In VSS, the secret information is recovered by human visual system or lightweight computational device. There are two models available in VSS, one is Visual Cryptography (VC) which is introduced by Naor's in 1994 and other is a Random Grid (RG) based VSS which is proposed by Keren and Kafri. This state of the art covers both the models of VSS along with its application. The various application areas of VSS are visual authentication and identification, image encryption, access control, data hiding etc. The chapter has also covered various future enhancements in VC based on cryptanalysis, optimal pixel expansion, multiple secret encoding, progressive VC etc. Random Grid based VSS have some advantages over VC, which eliminates the need of Pixel expansion and codebook. But still, there is scope for the improvements in the contrast and the complexity of exiting algorithms. So there are various challenges and opportunities which make it an exciting research area to work upon.Â